Experimental tests of precast reinforced concrete beam-column connections. Issue 125 (October 2019) - Guerrero, Hector; Rodriguez, Vladimir; Escobar, J. Alberto; Alcocer, Sergio M.; Bennetts, Felipe; Suarez, Manuel
Abstract: In the reinforced concrete (RC) precast industry there is great concern about the seismic behavior of connections that emulate monolithic ones. Therefore, an experimental program was developed to examine the seismic performance of a particular RC precast connection type frequently used in industrial applications in comparison to monolithic connections. Tests were conducted on full scale. This paper presents and discusses the main results. Comparisons of a benchmark monolithic connection and six precast beam-column joints are presented. Precast connections were fabricated using different detailing, various levels of joint confinement, and post-tensioning. Test results are compared in terms of strength and deformation capacity, energy dissipation, and stiffness degradation. A relation between effective beam stiffness and inter-storey drift is found and compared to cracked stiffness modification factors recommended by design codes. Two effective stiffness models for reinforced concrete beams are proposed. Conclusions relevant to the precast construction industry have been formulated. Results show an acceptable performance of the tested precast system for seismic applications. Highlights: Precast beam-column connections at full scale were tested under cyclic loading. Comparisons with a benchmark monolithic connection are shown. Deformation capacity, energy dissipation and stiffness degradation are presented. A relation between effective beam stiffness and inter-storey drift was found. The tested precast system showed acceptable performance for seismic applications.